Botany Recent Advances and Applications - Kumar Ghimire, Bimal (IntechOpen, 2021)
This book integrates knowledge of plant biotechnology, plant physiology, and the environment. It presents new information about soil organic carbon sequestration using plant species (tropical grasses) that have potential in climate change mitigation. It also presents scientific knowledge on the multipurpose role of microRNA (miRNA), focusing mainly on stress tolerance in crop plants. Chapters discuss uses, methods, and advantages of recombinant DNA technology and novel plant biotechnology applications for plant-based vaccines. This volume brings together knowledge about non-edible plants seeds as potential sources of biodiesel production to mitigate the global energy crisis.